2013
DOI: 10.2196/jmir.2422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Translation Process of an Internet-Based Self-help Intervention for Prevention of Depression: A Cost-Effectiveness Analysis

Abstract: BackgroundDepression is common and treatable with cognitive behavior therapy (CBT), for example. However, access to this therapy is limited. Internet-based interventions have been found to be effective in reducing symptoms of depression. The International Society for Research on Internet Interventions has highlighted the importance of translating effective Internet programs into multiple languages to enable worldwide dissemination.ObjectiveThe aim of the current study was to determine if it would be cost effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…However, 1 study targeting depression and anxiety provided broad information about costs of dissemination for the workshop leader (US $2000/10-15 participants), coaching emails, and face-to-face booster sessions (US $55/hour) [41]. To the author’s knowledge, no trials of technology-based interventions in tertiary students have examined cost-effectiveness per se, although there has been 1 study of the cost-effectiveness of translating the English-language program MoodGYM and the website BluePages for delivery to Norwegian university students [65]. This is not unexpected despite the argument that Internet-based research is useful at reducing the cost of public health, a recent review of all health-related Internet-based interventions, including mental health, found a total of only 8 studies that reported on cost-effectiveness [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, 1 study targeting depression and anxiety provided broad information about costs of dissemination for the workshop leader (US $2000/10-15 participants), coaching emails, and face-to-face booster sessions (US $55/hour) [41]. To the author’s knowledge, no trials of technology-based interventions in tertiary students have examined cost-effectiveness per se, although there has been 1 study of the cost-effectiveness of translating the English-language program MoodGYM and the website BluePages for delivery to Norwegian university students [65]. This is not unexpected despite the argument that Internet-based research is useful at reducing the cost of public health, a recent review of all health-related Internet-based interventions, including mental health, found a total of only 8 studies that reported on cost-effectiveness [66].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the cost-effectiveness of translation, researchers translated the Internet-delivered CBT programs BluePages and MoodGYM from English into Norwegian and conducted an RCT comparing the participants in the translated programs with wait-listed controls. 53 The cost of translation was about one-fourth the cost of a new program, and program implementation would produce a 21-fold return on investment based on the qualityadjusted life-years gained. These data support the translation of existing programs, rather than investment in the development of new programs.…”
Section: Box 4: Featured Program -Ocfightermentioning
confidence: 99%
“…In countries with iCBT, studies have shown that it can be remarkably successful in rural areas where access to mental healthcare is limited [55,61,66,67]. For countries that lack programs specific to their population and culture, well-researched programs can be adapted for a fraction of the cost of making a new program and still yield substantial gains [68]. iCBT provides treatment options for patients who cannot access treatment due to physical, psychological, or mobility issues [10].…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…It has been shown to be cost effective and reduce societal cost compared with waitlisted controls and in-person CBT [16,36,73]. As discussed above, it is relatively inexpensive to adapt an existing iCBT program [68], indicating that iCBT could potentially be implemented cost effectively.…”
Section: Limitations and Strengthsmentioning
confidence: 99%